The Margaret Chase Smith Essay: Can Maine Prosper? Leadership, Research, and Partnership for Economic Growth - Breen, Yellow (Maine Policy Review, 2017)
Yellow Light Breen examines how the Maine Development Foundation is working to help Maine’s economy through programs that focus on leadership, trusted research, and creative cross-sector partnerships.
Keywords: Maine Development Foundation; economic development